Korelasi Antara Kompetensi Sumber Daya Manusia Dengan Keberhasilan Proyek Konstruksi Pada Dinas Pekerjaan Umum Dan Penataan Ruang Provinsi Sumatera Utara - Putri, Ade Pradipta; Hasibuan, Gina Cynthia Raphita; Anas , M. Ridwan (Syntax Corporation, 2025)
The success of construction projects is influenced by many factors, one of which is the competence of human resources (HR). This study aims to analyze the influence of human resource competencies on the success of construction projects at the Public Works and Spatial Planning Office (PUPR) of North Sumatra Province. This study uses a quantitative method with a multiple linear regression approach on primary data obtained from 50 respondents from technical implementation units within the PUPR Office. The results show that the experience, loyalty, and certification of experts have a significant influence on the success of construction projects. These findings confirm the importance of strengthening human resource capacity through training and certification to improve overall project performance.